The Effect of the application of the Cooperative Learning Model Type Snowball Throwing Against an increase in the activity of learning to the learners on subjects Science in grade VII Inclusive SMPN 23 Padang - Eliza Octa Khairani; Ristiono Ristiono; Helendra Helendra; Resti Fevria (Universitas Negeri Padang, 2019)
The research was distributed by the low activity of learning to learners in an inclusive classroom while learning the IPA take place where student activity still centered on teachers so that students not actively in learning. This research aims to find out how big the influence of cooperative learning model type Snowball Throwing against learning activities learners in learning the IPA in the VII inclusive classroom junior high school 23 Padang. This type of research is the Quasy alphabets experiment using Control-Group design Only. This research was carried out in class VII2 as class experiments with the number of learners 32 people (with 3 learners ABK) and VII3 class as the class of the control to the number of learners 32 people (with 2 of HER students). The instruments used in the research in the form of the now learners learning activities that contains items of the statement drawn up in accordance with a predetermined indicators. Data analysis technique used is comparing the difference of two average learners with learning activities begins conducting a test of its homogeneity and normality, so that in the end done with test t (t-test).The average value of learning activities students class experiments is higher compared to the average value of learning activities learners class control. The average value of experimental class 76.41 and average value of kotrol class 70.08. Hypothesis test results data study activity learners class Sample thitung 2.67 and ttabel 1.67 its mean thitung > ttabel means then the hypothesis is accepted. This means that applying cooperative learning model type Snowball Throwing a positive effect against an increase in the activity of learning to the learners.